Ukraine and Beyond
XI, 291 p.
Keywords: This book is the first full-spectrum analysis of Russian and European norms of political action, ranging from international law, ethics, and strategy, to the specific norms for the use of force. It brings together leading scholars from these various fields, examining the differences in norm understanding between Russia and Europe. In light of the 2014 occupation and annexation of Crimea by Russia, and its subsequent covert participation in the internal affairs of Ukraine, including aggressive flying and major military exercises, Russia seems to be a classical revisionist power, intent on changing the balance of power in Europe in particular. It also reaches beyond Europe, inserting itself as the key actor in the Syrian war. The book therefore considers how we should understand Russia. It also questions whether or not the West, in particular Europe, responds adequately in this delicate and dangerous new situation. The book concludes that at present Russia acts strategically and with considerable success whereas Europe is reactive in its response. Janne Haaland Matlary is Professor of political science at the University of Oslo, Norway, and at the Norwegian Command and Staff College at the Defence University College in Oslo. Tormod Heier is Lieutenant Colonel in the Norwegian Army, and serves as a lecturer at the Norwegian Command and Staff College at the Defence University College in Oslo. .